Factors associated with mortality and complications in hypokalemic continuous ambulatory peritoneal dialysis patients - Wongluechai, Laddaporn; Peawponsong, Jirayupa (Journal of the Nephrology Society of Thailand, 2022)
Background: Patients with end stage renal disease treated with continuous ambulatory peritoneal dialysis (CAPD) presented complications from hypokalemia status. These led to septic peritonitis, peritoneal dialysis (PD) technique failure requiring changing the mode of renal replacement therapy to hemodialysis, involving malnutrition and increased mortality rate. Objectives: The study aimed to determine the prevalence of hypokalemia among patients with CAPD, and associated factors causing hypokalemia and peritoneal dialysis related complications including peritonitis, technical failure, hospitalization, and mortality. Methods: A retrospective study using descriptive analysis among patients with CAPD was conducted more than 6 months in the CAPD Clinic of Maharat Nakhon Ratchasima Hospital in fiscal year 2560. The patient’s demographic data, peritoneal dialysis prescription, medications, and serum potassium level were collected. PD related complications were collected among all patients and analyzed to compare between normokalemia and hypokalemia groups. Results: Totally, 400 patients with CAPD were included in this study with mean age 53 years. Males comprised 212 patients (53%) nearly equal to females. Diabetes mellitus and hypertension were the most common comorbidities in the normokalemia and hypokalemia groups. Hypokalemia occurred among 347 patients (86.6%) and the lowest mean potassium level was 2.4±1 mEq/L. No associations were found between age, sex, diabetes mellitus, medications, PD prescription, glucose exposure, and ultrafiltration with hypokalemia. Technique failure, and hospitalization significantly increased in the hypokalemia group; 16.4 compared with 5.7% (P=0.04), and 79.8 compared with 64.2% (P=0.02), respectively. Septic peritonitis or in terms of CAPD totaled 41.5% in the hypokalemia group and 34% in the normokalemia group, without significant difference. However, the total episodes of septic peritonitis and incidence of recurrent episodes increased in the hypokalemia group. Mortality did not differ between groups (24.5 and 20.8%, respectively, P = 0.69). The major cause of death and hospitalization were septic peritonitis. Conclusion: Hypokalemia increased among patients with CAPD and constituted an important problem. Hypokalemia increased the rates of septic peritonitis, technique failure, and hospitalization but without difference in mortality compared with normokalemia.